Studies of genetic, gastrointestinal, renal and dietary factors in white and black South African subjects as a possible key to understanding the relative absence of calcium oxalate kidney stone disease in the black population - Theka, Takalani P (Department of Chemistry, 2014)
The incidence of urolithiasis in South Africa's black population is extremely rare «1%) while in the white population it is similar to that of western countries (-15%). The present thesis was aimed at shedding more light on the complex nature of the physicochemical, biochemical and physiological mechanisms in black South Africans which provide this group with a natural protection against urolithiasis in contrast to their white compatriots. Four studies comprise this thesis.